واقع الشراكة بين الجامعات والمؤسسات الاقتصادية في الجزائر- رؤية استشرافية وإطار مقترح للإصلاح - - بوزيان, راضية (Université de M'sila, 2010)
The objective of this study is to try to find out the problematic of the relationship between Universities and Economic Institutions in Algeria, in order to identify the model of what is already available from the relationships between both parties, and monitoring some of the obstacles to effect participation between them, and suggest possible approaches to overcome these obstacles and graphic ways to reform.
Keywords: Partnership, the economic institution, forward-looking vision, the Reformation.